Front Street with man pulling cart at left, Nome, June 18, 1903 - Goetze, O. D. (Otto Daniel)
Caption on image: Front Street, Nome, Alaska. 545 Edward H. Mitchell, Publisher, San Francisco Filed in Alaska--Cities/Location--Nome